Морфологія пилкових зерен видів роду Crocus L. (Iridaceae Juss.) флори України - Kushnir, N.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2013)
The results of the study of morphological features of pollen grains of seven species of the genus Crocus L. are presented. The most stable indicators that can be used as an additional diagnostic features are picked out.